STRATEGI PROMOSI FILM WARKOP DKI REBORN: JANGKRIK BOSS! PART 1 - Syafrizal Setia Budi; Romdhi Fatkhur Rozi; Fajar Aji (ROLLING, 2018)
This research discusses the promotion strategy of Warkop DKI Reborn: Jangkrik Boss! Part 1 movie. Purpose of the research is to find out the creative ideas on strategy of getting the audience. Research data based on phases done by the Falcon Pictures promotion team, consists of preparation, action, and monitoring. It also explained the number of audiences gained based on promotional activities that have been done. This research uses qualitative methods with observation, interview, and literature study, that expected to show the effectiveness of promotions has made on the number of audiences that gained.